Has implementing an ecolabel increased sustainable tourism in Barcelona? - Arenado Rodríguez, Rocío; García López, Ana; Jiménez Caballero, José L. (Cuadernos de Turismo, 2017)
The aim of this study is to find out if by implementing an ecolabel in destinations, applying an SDM model, tourism sustainability increases. In order to this, three measures have been put into practice in Barcelona: (1) a focus group interview to key stakeholders (DMOs) see their implication with the certification project; (2) the implementations of two different actions relevant for the study: (a) to confront and pair up the certification body´s set of criteria with the Global Sustainable Tourism Council (GSTC) ones, (b) check if the certification adapts to Font´s study about ecolabels; and finally, (3) a discussion to find out if the media and local citizens felt in a city touristic ally sustainable. The findings show that Barcelona tourism board and other stakeholders were concerned about tourism sustainability. Besides, ecolabel can be believed to be trustworthy and reliable by adapting it to Font´s study (2001) and by confronting it with GSTC destination criteria. However, local population seems not to be satisfied at all with how the city is getting so many tourism. They seems not to understand labels, but they understand the negative impacts from tourism in their way of life. The limitation to this study is that just the Barcelona case is analyzed. The contribution is that it is actually putting into practice well known concepts that have usually been studied in theoretical ways.